Irene's Donut Is An Effective Method To Increase Knowledge, Attitudes And Actions Of Parents For Dental Hygiene Students - Salikun Salikun; Yodong Yodong; Hermien Rimbyastuti (Jurnal Riset Kesehatan, 2012)
This type of research is a quasi-experimental studies (Quasi Experimental). The study design is only one group pretest and postest design. Population research is the kindergarten students of Al Azhar 14 Semarang as many as 80 children with a sample of 30 students 30 students' parents. Data were analyzed using paired t-test different tests before and after counseling on each of the factors of knowledge, attitudes and practices of parents. The results showed no change increase in knowledge, attitudes and actions toward parents laying either after following the extension method Irene Donuts. This is also supported by test results satistik test statistic with paired t-test with p value = 0.001, with p value 0.008 and p value = 0.001 on the attitude that knowledge changes artimya no difference before and after counseling.